Myosins, Actin and Autophagy - Kruppa, Antonina; Kendrick-Jones, John; Buss, Folma (Wiley, 2019)
Myosin motor proteins working together with the actin cytoskeleton drive a wide range of cellular processes. In this review, we focus on their roles in autophagy - the pathway the cell uses to ensure homeostasis by targeting pathogens, misfolded proteins and damaged organelles for degradation. The actin cytoskeleton regulated by a host of nucleating, anchoring and stabilizing proteins provides the filament network for the delivery of essential membrane vesicles from different cellular compartments to the autophagosome. Actin networks have also been implicated in structurally supporting the expanding phagophore, moving autophagosomes and enabling efficient fusion with the lysosome. Only a few myosins have so far been shown to play a role in autophagy. Non-muscle myosin IIA functions in the early stages delivering membrane for the initial formation of the autophagosome, whereas myosin IC and myosin VI are involved in the final stages providing specific membranes for autophagosome maturation and its fusion with the lysosome.